Establishment of a five star hotel on the land of Bangladesh railway Jakir Hossain road, Chittagong - Hasan, Md. Taif (BRAC University, 2015)
This project report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2015.